(untitled) (Foro de Educacion, 2016)
This article explores the popular education movement in Latin America as an alternative political educational movement that took shape in the sixties and fully developed in the 1970s and early 1980s. It had its roots in the political culture in Latin America and developed a political pedagogical discourse that looked for alternative ways of doing politics, built meanings in the people’s culture, and aimed, by and large, at developing political consciousness from inside the political subject rather than externally revealed by the party.